2021
DOI: 10.1186/s12890-021-01717-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of intravenous immunoglobulin therapy in COVID-19 related acute respiratory distress syndrome: a retrospective cohort study

Abstract: Background Intravenous immunoglobulin (IVIG) has been used as an immunomodulatory therapy to counteract severe systemic inflammation in coronavirus disease 2019 (COVID-19). But its use in COVID-19 related acute respiratory distress syndrome (ARDS) is not well established. Methods We conducted a retrospective analysis of electronic health records of COVID-19 patients admitted to intensive care units (ICUs) at Hazm Mebaireek General Hospital, Qatar, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Studies' characteristics can be seen in Table 1 . From the 13 included studies, 7 were retrospective cohort studies 30 , 31 , 32 , 33 , 34 , 35 , 36 and 6 were prospective studies. 13 , 37 , 38 , 39 , 40 , 41 From the 6 prospective studies, 2 were randomised placebo controlled double‐blind trials, 2 randomised open‐label trials, 1 was a randomised placebo controlled open label trial and 1 was a non‐randomised open‐label prospective study.…”
Section: Resultsmentioning
confidence: 99%
“…Studies' characteristics can be seen in Table 1 . From the 13 included studies, 7 were retrospective cohort studies 30 , 31 , 32 , 33 , 34 , 35 , 36 and 6 were prospective studies. 13 , 37 , 38 , 39 , 40 , 41 From the 6 prospective studies, 2 were randomised placebo controlled double‐blind trials, 2 randomised open‐label trials, 1 was a randomised placebo controlled open label trial and 1 was a non‐randomised open‐label prospective study.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a recent meta-analysis performed by Xiang and colleagues confirmed the clinical efficacy of IVIGs by showing a favourable impact on survival in critically ill COVID-19 patients [ 28 ]. Nevertheless, the existing literature on IVIGs in COVID-19 is still controversial, which can be mainly explained by the high degree of heterogeneity in disease severity, different disease stages, small cohorts and a lack of standardized treatment regimens across the different studies [ 19 , 29 ]. In this context, a large randomized controlled trial could not demonstrate any benefit on outcome, but even a trend towards an increased frequency of serious adverse events [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This fact becomes particularly important because several other studies focused exclusively on patients already receiving mechanical ventilation at the start of IVIG treatment, thus focusing on later stages of the disease. In those studies, no clear evidence exists that IVIGs were effective in preventing disease progression or having a beneficial impact on survival [ 19 , 20 , 29 ]. In particular, a large randomized controlled trial from France showed no improved clinical outcome at day 28 by using IVIGs in patients already receiving mechanical ventilation [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 3 ] Angiotensin-converting enzyme-2 is normally secreted in upper and lower respiratory epithelial cells; thus, angiotensin-converting enzyme-2 stimulation in COVID-19 infection will significantly surge pro-inflammatory mediators and mucosal secretions, leading to dyspnea (breathlessness), cough, and throat pain. [ 4 , 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Angiotensin-converting enzyme-2 is normally secreted in upper and lower respiratory epithelial cells; thus, angiotensin-converting enzyme-2 stimulation in COVID-19 infection will significantly surge pro-inflammatory mediators and mucosal secretions, leading to dyspnea (breathlessness), cough, and throat pain. [4,5] This protein also acts as a pro-inflammatory mediator, which contributes to increased respiratory secretions in respiratory infections, and some of the other symptoms, predominantly, dyspnea, cough, and throat pain. [6,7] These symptoms variably respond to medical interventions such as oxygen therapy, oral opiates, ipratropium bromide and salbutamol nebulizers.…”
Section: Introductionmentioning
confidence: 99%